Marketing of Poultry Eggs-New Issues and Competitive Challenges - Srinivasa Reddy, P.; Venu Gopala Rao, Y. (Indian Journal of Marketing, 2011)
Indian poultry industry has registered a significant growth during the last four decades. India ranks fifth in the world with annual egg production of 1.61 million tonnes. Poultry exports are mostly made to Maldives and Oman. Indian poultry meat products have good markets in Japan, Malaysia, Indonesia and Singapore. Over all, Andhra Pradesh counts for maximum egg production. Within Andhra Pradesh, Hyderabad is the city with maximum poultry and hatcheries. Besides the state of Andhra Pradesh, Karnataka, Tamil Nadu, Maharashtra, Gujarat, Madhya Pradesh, Orissa and North Eastern States are the major egg contributors. Poultry egg processing units have come in a very big way in the country. Karnataka’s egg production accounts for 2.5 million eggs/day to 7.5 million eggs, that in Punjab expanded from 5.0 million 15.0 million eggs per day in the past two years. Tamil Nadu was producing 8.0 million eggs/day while Maharashtra 6.0m, Rajasthan 1.5m, Gujarat 2.5m, Madhya Pradesh 4.5m and Orissa 1.5m eggs per day. Egg output in the north-eastern states is estimated at 1.5m.